2009
DOI: 10.1007/s10750-009-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land use and black fly (Diptera, Simuliidae) species richness and species assemblages in tropical streams, Northeastern Thailand

Abstract: Habitat degradation through agricultural land use is the major factor threatening lotic ecosystems. Although black flies are major components of these ecosystems, the impact of agricultural land use on species diversity and species assemblages has been largely ignored in tropical streams of the Oriental region. The objectives of this study are to examine patterns of species distribution and species richness and to compare black fly species richness and species assemblages in forest and agricultural streams in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
3
37
1
1
Order By: Relevance
“…Day et al, 2008;Kúdela et al, 2014;Ilmonen et al, 2009), and the Oriental Region (e.g. Pramual and Adler, 2014;Pramual and Kuvangkadilok, 2009;Pramual et al, 2011). It has also been demonstrated that the COI barcoding region is a useful tool in revealing levels of genetic diversity in poorly known taxa, for example C. dissimilis, G.…”
Section: Craig and Cywinska (2012) Produced A Detailed Revision Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…Day et al, 2008;Kúdela et al, 2014;Ilmonen et al, 2009), and the Oriental Region (e.g. Pramual and Adler, 2014;Pramual and Kuvangkadilok, 2009;Pramual et al, 2011). It has also been demonstrated that the COI barcoding region is a useful tool in revealing levels of genetic diversity in poorly known taxa, for example C. dissimilis, G.…”
Section: Craig and Cywinska (2012) Produced A Detailed Revision Of The mentioning
confidence: 99%
“…Simuliid larvae consume dissolved organic matter in the water making it subsequently available to the food chain (Currie and Adler 2008;Malmquivist et al 2001Malmquivist et al 2004, and they are also an important food source for fishes and invertebrates (Currie and Adler 2008). In addition, black flies are important as indicators of freshwater contamination and stream degradation, because their immature stages are susceptible to both organic and inorganic pollution (e.g., Feld et al 2002;Pramual and Kuvangkadilok 2009 …”
mentioning
confidence: 99%
“…of allochthonous matter and, consequently, the communities and functional processes in lotic systems (Graça, 2001;Corbi and Trivinho-Strixino, 2008;Beltrão et al 2009;Casatti et al 2009;Pramual andKuvangkadilok, 2009, Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat degradation as a result of anthropogenic disturbance is a major impact threatening biodiversity worldwide (Pramual & Kuvangkadilok 2009); these authors examined black fly species richness and species assemblages in forest and agricultural streams in Thailand. Comparisons of the physicochemical conditions between forest and agricultural streams indicated that streams in agricultural areas are warmer with higher conductivity and fewer riparian trees.…”
Section: Discussionmentioning
confidence: 99%